Human Remains and Mass Violence Methodological Approaches - Dreyfus, Jean-Marc; Anstett, Élisabeth (Human Remains and Violence, 2014)
This book outlines for the first time in a single volume the theoretical and methodological tools for a study of human remains resulting from episodes of mass violence and genocide. Despite the highly innovative and contemporary research into both mass violence and the body, the most significant consequence of conflict - the corpse - remains absent from the scope of existing research.Why have human remains hitherto remained absent from our investigation, and how do historians, anthropologists and legal scholars, including specialists in criminology and political science, confront these difficult issues? By drawing on international case studies including genocides in Rwanda, the Khmer Rouge, Argentina, Russia and the context of post-World War II Europe, this ground-breaking edited collection opens new avenues of research.Multidisciplinary in scope, this volume will appeal to readers interested in an understanding of mass violence's aftermath.